Time to blood culture positivity as a predictor of clinical outcomes and severity in adults with bacteremic pneumococcal pneumonia. - Catia Cillóniz; Adrian Ceccato; Cristina de la Calle; Albert Gabarrús; Carolina Garcia-Vidal; Manel Almela; Alex Soriano; José Antonio Martinez; Francesc Marco; Jordi Vila; Antoni Torres (PLoS ONE)
Objectives We aimed to investigate the association between the time to positivity of blood culture (TTP) with clinical outcome and severity of pneumococcal bacteremic pneumonia. Methods Prospective observational study carried out in 278 hospitalized adult CAP patients with positive blood culture for Streptococcus pneumonia (2003-2015). Results A total of 278 cases of bacteremic pneumococcal pneumonia were analyzed, median age 62 (46; 79) years. Fifty-one percent of the cases had PSI IV-V. Twenty-one (8%) died within 30-days after admission. The analysis of the TTP showed that the first quartile of the TTP (9.2h) was the best cut-off for differentiating 2 groups of patients at risk, early (TTP <9.2 h) and late (TTP ≥9.2 h) detection groups (AUC 0.66 [95% CI 0.53 to 0.79]). Early TTP was associated with a statistically significant risk of invasive mechanical ventilation (18% vs. 6%, p = 0.007), longer length of hospital stay (12 days vs. 8 days, p<0.001), higher in-hospital mortality (15% vs. 4%, p = 0.010), and 30-day mortality (15% vs. 5%, p = 0.018). After adjustment for potential confounders, regression analyses revealed early TTP as independently associated with high risk of invasive mechanical ventilation (OR 4.60, 95% CI 1.63 to 13.03), longer length of hospital stay (β 5.20, 95% CI 1.81 to 8.52), higher in-hospital mortality (OR 5.35, 95% CI 1.55 to 18.53), and a trend to higher 30-day mortality (OR 2.47, 95% CI 0.85 to 7.21) to be a contributing factor. Conclusion Our results demonstrate that TTP is an easy to obtain surrogate marker of the severity of pneumococcal pneumonia and a good predictor of its outcome.